Analisis Penggunaan Fintech Syariah Perspektif Mashlahah Mursalah : (Studi Pada Dana Syariah.Id) - Muhammad Saleh; Andiny Utari; Abdul Wahab (Al-Buhuts, 2020)
This research is aimed to analyze the use of Sharia Fintech with the perspective of Mashlahah Mursalah on the Website and Dana Syariah.id Application. This type of research is a qualitative study with data sources are primary data obtained directly through the Website, application and interviews with syariah.id fund admin staff. Besides that it is also supported by secondary data obtained from literature studies. The analytical method uses descriptive analysis and content analysis in order to draw conclusions. The results of the research show that the use of syariah fintech applied by the syariah.id fund with crowd funding system has been officially registered and is inseparable from the supervision of the Sharia supervisory Board as well as OJK and DSN-MUI regulations. The easier and more efficient transaction process makes it attractive for customers to use services in syariah.id funds. This is indicated by the number of customers that have increased and the benefits that can be given in their transactions, minimizing all business risks, taking problems and keeping away from mudharat that is most important in accordance with the concept or perspective of the problematic mashlahah.